MODEL PEMBELAJARAN MENULIS TEKS DRAMA MENGGUNAKAN MEDIA TEKS CERPEN SISWA KELAS VIII - Ratnasari, Lili Lili; Ramadhan, Syahrul (Departemen Sastra Indonesia, 2020)
Various learning models and media can improve students' skills in writing drama texts. This study aims to describe the application of learning models to writing drama texts with short story media and to describe the ability to write student drama texts using short story text media. This research uses descriptive quantitative research design. The results showed that in general the learning model using short story text media was effectively used for learning to write drama texts.